Distal Sensory Peripheral Neuropathy in Human Immunodeficiency Virus Type 1–Positive Individuals Before and After Antiretroviral Therapy Initiation in Diverse Resource-Limited Settings. (12th August 2019) - Vecchio, Alyssa C; Marra, Christina M; Schouten, Jeffrey; Jiang, Hongyu; Kumwenda, Johnstone; Supparatpinyo, Khuanchai; Hakim, James; Sacktor, Ned; Campbell, Thomas B; Tripathy, Srikanth; Kumarasamy, Nagalingeswaran; La Rosa, Alberto; et al.
Abstract: Background: Distal sensory peripheral neuropathy (DSPN) is a complication of human immunodeficiency virus (HIV). We estimate DSPN prevalence in 7 resource-limited settings (RLSs) for combination antiretroviral therapy (cART)–naive people living with HIV (PLWH) compared with matched participants not living with HIV and in PLWH virally suppressed on 1 of 3 cART regimens. Methods: PLWH with a CD4+ count <300 cells/mm 3 underwent standardized neurological examination and functional status assessments before and every 24 weeks after starting cART. Matched individuals not living with HIV underwent the same examinations once. Associations between covariates with DSPN at entry were assessed using the χ 2 test, and virally suppressed PLWH were assessed using generalized estimating equations. Results: Before initiating cART, 21.3% of PLWH had DSPN compared with 8.5% of people not living with HIV (n = 2400; χ 2 (df = 1) = 96.5; P < .00001). PLWH with DSPN were more likely to report inability to work [χ 2 (df = 1) = 10.6; P = .001] and depression [χ 2 (df = 1) = 8.9; P = .003] than PLWH without DSPN. Overall prevalence of DSPN among those virally suppressed on cART decreased: 20.3%, week 48; 15.3%, week 144; and 10.3%, week 192. Incident DSPN was seen in 127 PLWH. Longitudinally, DSPN was more likely in older individuals ( P < .001) and PLWH with less education ( P = .03). There was no significant association between cART regimen and DSPN. Conclusions: Although the prevalence of DSPN decreased following cART initiation in PLWH, further research could identify strategies to prevent or ameliorate residual DSPN after initiating cART in RLSs. Abstract : We compared the prevalence of distal sensory peripheral neuropathy in 860 people living with human immunodeficiency virus who were antiretroviral therapy (ART) naive from multiple low-resource countries to that of 2400 HIV– matched controls. The HIV+ participants were randomized to 3 antiretroviral regimens. There was a higher prevalence of neuropathy among the HIV+ participants, which improved following the initiation of ART with subsequent viral suppression. There was no relationship with treatment arm.